Nonlinear Electron Phase‐Space Dynamics in Spontaneous Excitation of Falling‐Tone Chorus. Issue 18 (16th September 2022) - Wu, Yifan; Tao, Xin; Zonca, Fulvio; Chen, Liu
Abstract: Whistler mode chorus, characterized by frequency chirping, is an important type of waves in planetary magnetospheres. To investigate the role of nonlinear wave particle interactions in excitation of chorus, analysis of electron phase space dynamics is required. While electron phase hole associated with rising tone chorus has been well studied, the phase space structure corresponding to falling tone chorus is less understood. Here, we investigate in detail the electron phase space dynamics in a spontaneously generated falling tone chorus with a parabolic type magnetic field, where field strength decreases away from the equator. We demonstrate the formation and evolution of electron phase space clump from downstream to upstream regions, and show that the variation of frequency chirping rate is caused by the movement of the source region. The results are consistent with the recently proposed Trap‐Release‐Amplify model, and should be useful to understand the mechanism of chorus frequency chirping. Plain Language Summary: Chorus is a type of important electromagnetic waves frequently observed in planetary magnetospheres. It is named after its sound while played through a loudspeaker. The particular sound is related to frequency chirping, meaning the wave frequency increases or decreases rapidly with time. Scientists have been debating the frequency chirping mechanism for more than half a century. One important conclusion emerging from previous theoretical studies is about the existence of two types of phase space structures: the phase space hole and the phase space clump associated with rising‐tone and falling‐tone chorus, respectively. While the former has been verified by many computer simulations, the latter has not been well studied. In this work, we use first‐principle computer simulations to investigate, for the first time, the formation and evolution of phase space clump in excitation of spontaneous falling tone chorus. We also propose the variation of chirping rate within chorus element is related to the movement of source region, where phase space structures are released from the wave packet. We find that our simulation results agree very well with the recently proposed "Trap‐Release‐Amplify" model of chorus. Key Points: We use a Particle‐In‐Cell simulation to demonstrate the formation of phase space clump in excitation of falling tone chorus We prove that electron phase space clump evolves in a way consistent with the Trap‐Release‐Amplify model Our results show that the variation of chirping rate within an element could be explained by the movement of source region